Hybrid analysis (barcode-high resolution melting) for authentication of Thai herbal products, Andrographis paniculata (Burm.f.) Wall.ex Nees - Osathanunkul, Maslin (Pharmacogn Mag, 2016)
BACKGROUND: Andrographis paniculata Nees is a medicinal plant with multiple pharmacological properties. It has been used over many centuries as a household remedy. A. paniculata products sold on the markets are in processed forms so it is difficult to authenticate. Therefore buying the herbal products poses a high-risk of acquiring counterfeited, substituted and/or adulterated products. Due to these issues, a reliable method to authenticate products is needed. MATERIALS AND METHODS: High resolution melting analysis coupled with DNA barcoding (Bar-HRM) was applied to detect adulteration in commercial herbal products. The rbcL barcode was selected to use in primers design for HRM analysis to produce standard melting profile of A. paniculata species. DNA of the tested commercial products was isolated and their melting profiles were then generated and compared with the standard A. paniculata. RESULTS: The melting profiles of the rbcL amplicons of the three closely related herbal species (A. paniculata, Acanthus ebracteatus and Rhinacanthus nasutus) are clearly separated so that they can be distinguished by the developed method. The method was then used to authenticate commercial herbal products. HRM curves of all 10 samples tested are similar to A. paniculata which indicated that all tested products were contained the correct species as labeled. CONCLUSION: The method described in this study has been proved to be useful in aiding identification and/or authenticating A. paniculata. This Bar-HRM analysis has allowed us easily to determine the A. paniculata species in herbal products on the markets even they are in processed forms. SUMMARY: We propose the use of DNA barcoding combined with High Resolution Melting analysis for authenticating of Andrographis paniculata products. The developed method can be used regardless of the type of the DNA template (fresh or dried tissue, leaf, and stem). rbcL region was chosen for the analysis and work well with our samples. We can easily determine the A. paniculata species in herbal products tested. Abbreviations used: bp: Base pair, Tm: Melting temperature